Quaternion-Based Non-Singular Terminal Sliding Mode Control of Quadrotor with a Two-Degree-of-Freedom Deformable Arm for Narrow Environments - Luwei Liao; Zhong Yang; Xu Chen; Haoze Zhuo; Hongyu Xu; Nuo Xu; Danguo Cheng (Drones)
Conventional multi-rotors with limited deformation capability are unable to meet the traversal capability of complex and narrow environments. In order to solve the above problems, a novel type of deformable quadrotor with a two-degree-of-freedom arm, named QTDA, is proposed. Firstly, the overall structural design of the QTDA is introduced, and its movement strategy is analyzed. Secondly, the Newton–Euler equations based on a quaternion are utilized to model the omnidirectional dynamics and kinematics of the system. Next, to tackle the multi-actuator control problem, a pseudo-inverse control allocation method is developed, along with an analysis of control allocation singularities. Furthermore, non-singular terminal sliding mode position control law and non-singular terminal sliding mode attitude control law based on a quaternion are designed. Finally, simulations are conducted to verify the effectiveness of the proposed control methods. The results demonstrate the QTDA’s ability to traverse both narrow horizontal and vertical environments, thereby validating the effectiveness of the approach presented in this paper.